Comparison between the soil chemical atributes sampled conventionaly and in grid - Ferraz, Gabriel Araújo e Silva; Silva, Fábio Moreira da; Oliveira, Marcelo Silva de; Silva, Flávio Castro da; Carvalho, Luis Carlos Cirilo (Coffee Science - ISSN 1984-3909, 2017)
The aim in this article was to characterize the structure and magnitude of the spatial distribution of soil attributes on a coffee field and map these attributes in order to identify the spatial dependence of them. It was aimed to compare the attribute amount when it was sampled conventionally or in grid sampling. This study was carried out on the Brejão farm in Três Pontas, Minas Gerais state, Brazil. As a data base were used pH, P, Prem, K, Ca, Mg, Al, H + Al, m, T, t, SB, V e MO sampled conventionally or sampled in a 64 point squared grid georeferenced with 36 points from grid zoom as well. The analysis of these data by geostatistics tools allowed characterize the spatial variability which allowed creating maps of spatial distribution of the variables. It was possible to identify differences presented in the amount of soil attributes sampled conventionally and in georreferenced grid sampling in precision coffee culture.